THE EFFECTIVENESS OF MODERN TEACHING STRATEGIES FROM THE PERSPECTIVE OF INTERMEDIATE SCHOOL TEACHERS IN KIRKUK GOVERNORATE - Al-Bayati, Kareem Ahmed Mohammed; Ahmed, Sufyan Hasan; Khammas, Mohanad Yousif (Journal of Learning on History and Social Sciences, 2025)
Objective: The study aimed to explore the effectiveness of modern teaching strategies in enhancing teacher performance in Kirkuk Governorate, while also analysing the impact of certain demographic variables, including gender, academic qualifications, and years of experience, on the adoption of these strategies. Method: The researcher used the descriptive analytical approach, and the study was conducted on a sample of 130 male and female teachers from schools in Kirkuk Governorate. Data was collected using a questionnaire consisting of 26 items divided into three axes: the first axis contains 10 items related to teachers' perceptions of the effectiveness of modern teaching strategies; the second axis includes 10 items related to the challenges of implementing these strategies; and the third axis contains six items related to the impact of these strategies on student performance. Results: The study results showed a moderate to high positive trend toward the use of modern teaching strategies, with an overall mean of 3.86, reflecting an overall agreement rate of 77.2%. It also showed no statistically significant differences between male and female teachers or between teachers with different academic qualifications in their opinions about these strategies. However, the study revealed statistically significant differences according to years of experience, with teachers who had more experience holding more positive views about the effectiveness of these strategies. Novelty: The study uniquely highlights the role of years of teaching experience in shaping teachers’ positive perceptions of modern teaching strategies, while demonstrating that gender and academic qualifications do not significantly influence these perceptions.